Strategic spatial planning in the implementation of mobility hubs - Kristina Trygg; Ida Grundel (Journal of Urban Mobility)
A challenge for urban planning is the transition away from private car use towards other more sustainable transport modes, moving from urban policies and planning approaches to the implementation of sustainable mobility alternatives. This paper addresses how four Swedish municipalities are implementing new mobility solutions in transport infrastructure through the example of mobility hubs. The use of mobility hubs as a planning tool is a relatively new way of designing and combining different transportation modes, focusing on sharing options, e.g., bikes, e-scooters, car-sharing, etc., as well as public transport to reduce car dependency in cities (Czarnetzki & Slek, 2022; Rongen et al., 2022). The aim of this paper is to explore how municipal planners use mobility hubs strategically to achieve sustainable mobility. Our empirical material is based on interviews and workshops with planners, as well as an analysis of policy documents in four Swedish municipalities (between 2020 and 2022). We use strategic spatial planning as a framework to examine and understand the planning processes around mobility hubs. Our results show that although the overall aim in all municipalities is to reduce car dependency, there are spatial differences in how and where the mobility hubs are located, designed, and defined. This will have consequences for whom they are developed, and how they can strengthen socio-spatial relations and mobility justice. There was also a lack of consensus on the definition of mobility hubs, both between and within the municipalities under study. As a result of the inconsistencies in the implementation of mobility hubs between the municipalities, the municipal planners are not convinced of the effectiveness and appropriateness of the ways mobility hubs are currently being implemented.